Where do we go from here? Innovative technologies and heritage engagement with the MakerBus. (September 2017) - Compton, Mary E.; Martin, Kimberley; Hunt, Ryan
Abstract: The MakerBus project, based out of London, Ontario, provides an interesting springboard for exploring multifaceted concepts of archaeological and heritage engagement. The MakerBus, a 1989 school bus-cum-digital lab and creative play-space on wheels, utilizes various technologies often affiliated with the 'maker movement' such as virtual reality and augmented reality viewers, UAVs (drones), 3D scanners, and 3D printers, in order to explore subjects not central to the traditional 'maker' remit, namely those of the humanities and social sciences. Though not explicitly a public archaeology or heritage project, the MakerBus philosophy advocates for community driven, hands-on, peer-to-peer learning, and our team members have participated in public archaeology and local heritage events. This paper will give a brief overview of the 'maker movement' and the development of the MakerBus project, and will then discuss how the project speaks to issues of meaning-making, knowledge production, and information sharing in digital archaeological heritage practice. Highlights: A brief overview an innovative heritage outreach initiative (MakerBus) is provided. Maker technologies democratise access to technologies typically reserved for experts. Mobilizing maker technologies can change archaeological and heritage engagement. Through making, people are not just consumers of information, but also producers.